Depressive and anxiety symptoms and associated factors among postnatal women in Enugu-North Senatorial District, South-East Nigeria: a cross-sectional study - Olaoluwa S. Agbaje; Joy I. Anyanwu; Prince I. C. Umoke; Tochi E. Iwuagwu; Cylia N. Iweama; Eyuche L. Ozoemena; Ijeoma R. Nnaji (BMC, 2019)
Abstract Background Postnatal depression (PND) and anxiety (PNA) among women are prevalent and impairing health problems, with adverse outcomes for mothers and their infants. This study assessed the prevalence of depression, anxiety and associated factors in a sample of postnatal women. Method A community-based cross-sectional study was conducted on 270 postpartum women attending public health facilities in the study area. Postnatal depression was measured using the Edinburgh Postnatal Depression Scale (EPDS) and anxiety was measured using the Hospital Anxiety and Depression Scale (HADS-A). Data on maternal demographics, health characteristics, pregnancy-related characteristics, labor and birth characteristics, were collected via structured questionnaire. Binary Logistic and multinomial logistic regression analyses were carried out to identify the factors associated with depressive and anxiety symptoms in women. Results The EPDS identified 92 women (34.6%) as possibly depressed (using a cut-off ≥13) while the HADS-A identified 89 women (33.3%) with anxiety symptoms (using a cut-off + 8). A total of 69 women were identified with symptoms of anxiety and depression (anxious-depression). The multinomial regression analysis (MLA) showed that the history of depression (AOR = 0.12, 95% (CI 0.02, 0.76), and being a mother aged 15-29 years (AOR = 10.31, 95% (CI 1.13, 94.11) had a significant effect on the development of anxiety symptoms in women. Although not significant, mother's income level (AOR = 1.53, 95% (CI 0.72, 3.25), and being a younger mother (AOR = 1.06, 95% (CI 0.21, 5.26) were more likely to predict depressive symptoms in postnatal women. Attendance at postnatal care services in the PHCs (AOR = 0.14, 95% CI (0.04, 0.48) was significantly associated with anxious-depressed in the studied postnatal women. Conclusion The findings of this study showed a direct association between depressive symptoms, anxiety and younger maternal age, rural residence, and low income. The higher prevalence of depressive and anxiety symptoms in this study is a call for postnatal care that is culturally sensitive, patient-centered, accessible and affordable by women, most importantly poor and rural women.